2019
DOI: 10.2196/11065
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mothers’ Perceptions of a Technology-Based Supportive Educational Parenting Program (Part 2): Qualitative Study

Abstract: Background Transitioning into parenthood can be stressful as parents struggle to cope with new parenting responsibilities. Although perinatal care in hospitals aims to improve parental outcomes, there is a general consensus that it is suboptimal and insufficient. Therefore, many studies have designed intervention methods to supplement support for parents during this stressful period. However, studies often focus on parental outcomes as indicators of their interventions’ success and effectiveness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 62 publications
(77 reference statements)
3
13
0
Order By: Relevance
“…These results are highly consistent with those of other studies that showed that enhancing the training of professionals, especially in mental health areas, is imperative [65]. In addition, more multiple professional services should be provided within the first months postpartum [12,66].…”
Section: Discussionsupporting
confidence: 91%
“…These results are highly consistent with those of other studies that showed that enhancing the training of professionals, especially in mental health areas, is imperative [65]. In addition, more multiple professional services should be provided within the first months postpartum [12,66].…”
Section: Discussionsupporting
confidence: 91%
“…These phenomena had also been observed in other countries, such as America, where mothers receive little professional guidance in the 6 weeks after delivering a baby [65]. Therefore, multiple professional services should be provided during the first months postpartum [11,66].…”
Section: Discussionmentioning
confidence: 61%
“…These phenomena had also been observed in other countries, such as America, where mothers receive little professional guidance in the 6 weeks after delivering a baby [66]. Therefore, multiple professional services should be provided during the rst months postpartum [12,67].…”
Section: Discussionmentioning
confidence: 62%